4‐Hydroxy‐3‐methyl‐6‐(1‐methyl‐2‐oxoalkyl)pyran‐2‐one Synthesis by a Type III Polyketide Synthase from Rhodospirillum centenum. Issue 8 (22nd April 2013) - Awakawa, Takayoshi; Sugai, Yoshinori; Otsutomo, Kanae; Ren, Shukun; Masuda, Shinji; Katsuyama, Yohei; Horinouchi, Sueharu; Ohnishi, Yasuo
Abstract The purple photosynthetic bacterium Rhodospirillum centenum has a putative type III polyketide synthase gene (rpsA). Although rpsA was known to be transcribed during the formation of dormant cells, the reaction catalyzed by RpsA was unknown. Thus we examined the RpsA reaction in vitro, using various fatty acyl‐CoAs with even numbers of carbons as starter substrates. RpsA produced tetraketide pyranones as major compounds from one C10–14 fatty acyl‐CoA unit, one malonyl‐CoA unit and two methylmalonyl‐CoA units. We identified these products as 4‐hydroxy‐3‐methyl‐6‐(1‐methyl‐2‐oxoalkyl)pyran‐2‐ones by NMR analysis. RpsA is the first bacterial type III PKS that prefers to incorporate two molecules of methylmalonyl‐CoA as the extender substrate. In addition, in vitro reactions with 13C‐labeled malonyl‐CoA revealed that RpsA produced tetraketide 6‐alkyl‐4‐hydroxy‐1, 5‐dimethyl‐2‐oxocyclohexa‐3, 5‐diene‐1‐carboxylic acids from C14–20 fatty acyl‐CoAs. This class of compounds is likely synthesized through aldol condensation induced by methine proton abstraction. No type III polyketide synthase that catalyzes this reaction has been reported so far. These two unusual features of RpsA extend the catalytic functions of the type III polyketide synthase family.